Community involvement in management for maintaining coral reef resilience and biodiversity in southern Caribbean marine protected areas (2008)
Climate change is posing new challenges to conservation because management policies on protected coral reefs are less eVective than they were before the current ecosystem degradation. Coral reefs, the most diverse and complex marine ecosystem provide economic services for millions, but are seriously threatened worldwide because reef-building corals are experiencing bleaching phenomena and a steady decline in abundance. The resources of a Marine Protected Area (MPA) in Cartagena, Colombia, are in constant decline, despite a current management plan and on-site staV, urging new conservation actions. A multidisciplinary team gathered to evaluate management eVectiveness including biophysical, socioeconomic and governance indicators. Coral cover and Wsh diversity and abundance were low both inside and outside the MPA, which suggests a limited eYciency of management. Currently, the MPA is a reef with low coral cover and high algae cover as well as large dead coral areas, which are generally signs of highly degraded reef habitats. Live coral cover in the MPA was represented by pioneer coral species such as Agaricia tenuifolia and Porites astreoides. Nonetheless, 35% of the scleractinian species sampled in the area harbored more than one zooxanthellae symbiont, which suggests potential resistance and resilience against coral bleaching. Maintenance of trophic structure and functional diversity is an important endeavor that should be a priority for management in order to allow ecosystem resilience. Social and governance indicators showed low-income levels and few opportunities for communities living in and around the park, low governability, weak communication among stakeholders and with authorities at diVerent levels. As a result, problems related to over exploitation of resources were commonplace in the MPA. These results reXect low adaptive capacity of communities to comply with restrictive conservation rules, showing that establishment of a protected area is a necessary but insuYcient condition to guarantee conservation goals. Ignoring the role of local communities only will exacerbate the problems associated with natural resources. Involvement of communities in strategic ecosystems management appears to be a requisite to improve eVectiveness of protected areas, and participatory strategies, such as co-management, oVer opportunities to improve governability while letting communities adapt to MPA needs.